2011
DOI: 10.1586/era.11.113
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes data for accelerated partial breast irradiation using balloon brachytherapy

Abstract: Accelerated partial breast irradiation has been investigated in selected patients with early-stage breast cancer. Accelerated partial breast irradiation limits the radiation target to the volume of tissue immediately surrounding the lumpectomy cavity and reduces the overall treatment time from approximately 6 weeks to 5 days. Balloon brachytherapy was introduced in 2000. Since that time, several clinical experiences have demonstrated excellent outcomes in carefully selected patients. Modern intracavitary brach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Single-institution and registry studies reported to date with short follow-up show risks of local recurrence similar to those associated with wholebreast radiation. 24,25 Although the results of one population-based study in older women provides a cautionary note by showing that women treated with APBI have a higher rate of subsequent mastectomy than those treated with whole-breast radiation, this rate was still very low. 26 A national clinical trial comparing whole-breast radiation and APBI has enrolled thousands of women, but results will not be available for a few years.…”
Section: Radiation: More Of Lessmentioning
confidence: 99%
“…Single-institution and registry studies reported to date with short follow-up show risks of local recurrence similar to those associated with wholebreast radiation. 24,25 Although the results of one population-based study in older women provides a cautionary note by showing that women treated with APBI have a higher rate of subsequent mastectomy than those treated with whole-breast radiation, this rate was still very low. 26 A national clinical trial comparing whole-breast radiation and APBI has enrolled thousands of women, but results will not be available for a few years.…”
Section: Radiation: More Of Lessmentioning
confidence: 99%
“…This involves using fewer, larger-dose radiation or brachytherapy techniques to achieve the same effect. There are currently many trials which are assessing the effectiveness and safety of this procedure [17][18][19][20][21][22] . However, from preliminary data it seems reasonable to consider these methods as a valid alternative to omitting adjuvant radiotherapy in elderly patients with early stage breast cancer.…”
mentioning
confidence: 99%